Enhancing Vocabulary Acquisition and Retention Through the Brain-Based Learning Strategies - Kandasamy, Kasturi; Ibrahim, Noor Aireen; Jaafar, Haliza; Hanafi Zaid, Yasmin (AJELP: Asian Journal of English Language and Pedagogy, 2021)
The aim of this study was to assess the effectiveness of the Brain-based Learning Approach in enhancing vocabulary acquisition and retention among Year 4 pupils in a primary school. The strategy implemented was based on Brain-Based Learning Principles. The goal of Brain-based education is to make the utmost use of the situations in which the brain learns the best. Hence, it can be said that brain-based learning in the classroom demonstrates an innovative approach which enhances positive learning conditions for school children. Vocabulary acquisition is an important component in second language acquisition, and it becomes more meaningful when retention of the words learnt is maximized. Embedding brain-based learning strategy in teaching and learning provides opportunity for better vocabulary acquisition and retention, at the same time, increases the level of motivation among young learners. A descriptive quantitative design was used in this study involving 33 pupils from a primary school in Batu Pahat, Johor. The pupils had average to above average English language proficiency and were randomly allocated in the control group and the experimental group. The control group had undergone traditional approach to learning vocabulary while the experimental group experienced learning which encompassed brain-based learning approach. The pupils in both groups underwent a pre-test, post-test and delayed post-test. Data derived from these tests were analysed and tabulated for mean and percentage. The independent t-test showed significant difference in vocabulary acquisition and retention among pupils in both groups. It was found that pupils who followed the brain-based teaching approach attained better vocabulary acquisition and vocabulary retention compared to the pupils who were exposed to traditional teaching methods.